PENGARUH LEVERAGE, SIZE, AGE, DAN CASH FLOW TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR - Setiawan, Fedra Valeria; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to find out empirically how the influence of leverage, firm size, firm age, and cash flow on financial performance of manufacturing companies in the non-cylical consumption sector period 2017-2020. The sample collection method used is judgement sampling with 31 manufacturing companies and 124 total observations of manufacturing companies data. This research uses Eviews version 12.0 as a data processing software. This study shows results that cash flow have a positive effect on financial performance, but leverage, firm size, and firm age have no effect on financial performance.